2011
DOI: 10.1007/s00441-011-1273-8
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional studies of Prop1-expressing cells in the rat pituitary primordium of Rathke's pouch

Abstract: Pituitary embryonic development progresses daily toward terminal differentiation exhibiting quantitative and qualitative alterations regulated by signal molecules and transcription factors expressed under temporospatial control. In this study, we analyzed the heterogeneity of the cells in the pituitary primordium of embryonic day (E) 13.5. The three-dimensional structure of the Rathke's pouch was built up from measurements taken from multiple DAPI-stained sections and cell populations positive to stem/progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The expression of the organ-specific factors Prop1 and Pit-1 may reveal a cell population at a committed precursor stage in the course of differentiation to a specific cell type (54). The mRNA levels of these markers displayed an interesting increase in the MZ and AP in AT and in the early and active lactancy groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The expression of the organ-specific factors Prop1 and Pit-1 may reveal a cell population at a committed precursor stage in the course of differentiation to a specific cell type (54). The mRNA levels of these markers displayed an interesting increase in the MZ and AP in AT and in the early and active lactancy groups.…”
Section: Discussionmentioning
confidence: 98%
“…The Sox9 progenitor marker, a member of the SoxE subfamily, is important in embryonic and postnatal development (9) and participates in differentiation programs by activation of tissue-specific genes (26). In the pituitary gland, it has been postulated that the transcription factor Prop1 might play a role as a trigger in the terminal differentiation process of progenitor cells, leading to the development of endocrine cells (53,54). Prop1 positively regulates the expression of the pituitary-specific transcription factor Pit-1, with this factor being critical for normal thyrotroph, somatotroph, and lactotroph development.…”
mentioning
confidence: 99%
“…Other molecules play relevant roles in the development of the CNS, including the SOXB1 TFs (SOX1, SOX2 (Yako et al 2011) and SOX3 (Woods et al 2005)). SOX3 expression begins during early embryogenesis; recent studies have suggested that this gene must be expressed at a constant level because both increases and decreases in its expression are related to pituitary deficiencies and CNS malformations (Woods et al, 2005).…”
Section: Early Organogenesis: Rathke's Pouch Invaginationmentioning
confidence: 99%
“…The WNT (Yako et al 2011) and SHH pathways (Fernandez-Rodriguez et al 2011) are important for proliferation regulation, while the BMP and FGF pathways are required for proliferation and for determining cellular migration (Kato et al 2010). Rathke's pouch formation is complete at approximately E10 .…”
Section: Early Organogenesis: Rathke's Pouch Invaginationmentioning
confidence: 99%
See 1 more Smart Citation